Mask etiquette amidst COVID-19 crisis and personal protection equipment shortage - Gaurav Salunke; S K Biswas; Vivek Bhat (Indian Journal of Medical and Paediatric Oncology)
The COVID-19 virus is transmitted through close contact between people, via droplets and possibly via airborne transmission. Wearing a mask is one of the recommended preventive measures that can reduce the transmission of COVID-19. But due to panic buying and increased demands, the health institutes are facing severe shortages of these PPEs. This article reviews the types of masks available, the feasibility of reusing them and the dos and don'ts of each suggested method.